Application of Projected Unit Credit Method (PUC) and Entry Age Normal (EAN) in Pension Fund Calculation - Hidayat, Agus Sofian Eka; Maharani, Ni Kadek Gita; Hapsari, Nayla; Ajeng, Aprilia (President University, 2025)
This study explores the application of the Projected Unit Credit (PUC) and Entry Age Normal (EAN) methods in calculating normal cost and actuarial liability for pension funds. By comparing the two methods, the research aims to provide insights into their implications for pension fund management. The PUC method, which takes into account salary growth over time, typically results in increasing normal cost and smaller actuarial liability as the participant's service period lengthens. Conversely, the EAN method spreads the pension cost evenly over an employee's working years, leading to stable normal cost and higher actuarial liability, particularly in the mid-period of membership. The study utilizes data from PT. XYZ, applying both methods separately for male and female participants due to differences in life expectancy. The results offer a comparative analysis that highlights the financial implications of each method for both participants and pension fund companies, contributing to more effective pension fund management strategies.